Discourse on Alternative Contextual Evangelism Models to The Bolaang Mongondow Tribe as An Unreached People Group in North Sulawesi - Marde Christian Stenly Mawikere; Christie Garry Mewengkang (Sekolah Tinggi Theologia Jaffray, 2020)
This article is a historical study of alternative contextual evangelism models to Intau(means“person”)Bolaang Mongondow, which is communally called tribe or society (ethnic group/people group) Bolaang Mongondow.This study uses a literature review approach. It begins with researching the religion and beliefs of Intau Bolaang Mongondow. Then proceed with the socio-cultural phenomena of Intau Bolaang Mongondow, namely the dynamics of acculturation, openness to external influences, public attitudes towards change, and its essential element to determine alternative contextual evangelistic approaches.This study's final results show that attention to culture in developing a contextual evangelistic approach does not mean that the church must conform fully or assume harmony between the Gospel and culture. It is precisely by understanding and utilizing culture in the preaching of the contextual Gospel that it will be seen that Christian values have an advantage regarding the guarantee of eternal salvation in the Lord Jesus Christ. Therefore, efforts to prepare a contextual evangelist who has integrity, character, and competence regarding the Bible and culture are significant. Likewise, efforts to pioneer and develop contextual churches in the Intau Bolaang Mongondow environment must touch and empower those cultural values.